Implementation of Problem Based Learning Model to Improve Learning Outcomes at SD Negeri Lawe Bulan - Suriani, Irma Fitri (DEEP LEARNING: Journal of Educational Research, 2025)
This classroom action research aims to improve the learning outcomes of fourth-grade students at SD Negeri Lawe Bulan in the topic of "Approaching Puberty" through the implementation of the Problem Based Learning (PBL) model. The study is motivated by the low academic performance observed in students, which fell below the Minimum Competency Standard. The conventional and monotonous learning methods were identified as contributing factors to students’ lack of engagement and understanding, particularly in Islamic religious education, where concepts are often delivered as rote memorization. The research was conducted in two cycles, each consisting of planning, action, observation, and reflection. Data collection techniques included tests, observations, and documentation. The findings indicate that PBL significantly enhanced students' critical thinking, engagement, and learning outcomes. In Cycle I, the average student score was 77.92, while in Cycle II, it increased to 86.28. Student and teacher activities during learning also improved from "good" to "very good" qualifications. The PBL model, by incorporating real-life problems and collaborative learning, created a more meaningful learning experience and promoted students’ active participation. This approach helped students better understand the physical and emotional changes associated with puberty and encouraged them to take responsibility for their learning. The results of this study demonstrate that PBL is an effective instructional model to foster deeper comprehension, critical thinking skills, and improved academic performance in religious education. It also supports the development of independent, creative, and responsible learners.